Impact of Rotation on Heated Couple-Stress Ferromagnetic Fluid in a Variable Gravity Field - Anil Kumar; Ram Bharat Singh; Mamta Barik; Pankaj Goel; Depti Seth (Utilitas Mathematica, 2025)
The thermosolutal instability of a couple-stress ferromagnetic fluid subjected to rotation and varying gravity is explored through a linear stability analysis. The fluid layer, heated and soluted from below, is confined between two free surfaces. Using the normal mode technique, an exact solution for the stability of the couple-stress ferromagnetic fluid is derived. The critical Rayleigh number for the onset of instability is established using both numerical and graphical methods. In the case of stationary convection, a stable solute gradient acts to stabilize the system, while couple-stress effects can either stabilize or destabilize the fluid under certain conditions. Magnetization stabilizes the system regardless of rotation when there is no steady solute gradient. Additionally, the principle of exchange of stabilities applies under specific conditions where both rotation and a stable solute gradient are absent.